2018
DOI: 10.1016/j.humpath.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes associate with outcome in nonendemic nasopharyngeal carcinoma: a multicenter study

Abstract: The prognostic significance of tumor-infiltrating lymphocytes (TILs) has been studied recently in many cancers. For the first time in a nonendemic region, we have evaluated the prognostic value of TILs in a whole population-based nationwide cohort of nasopharyngeal carcinoma (NPC) in Finland. A total of 115 cases from Finnish hospitals were included. TILs were analyzed using hematoxylin and eosin-stained slides according to the criteria of the International Immuno-Oncology Biomarker Working Group. TILs were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
3
35
1
Order By: Relevance
“…We found that stromal categorization that was based on the assessment of tumor-stroma ratio and stromal TILs can serve as a robust tool for prognostication of early OTSCC. Importantly, these two stromal characteristics have shown promising prognostic significance in different subsites of the head and neck cancer [15,[25][26][27][28][29]. We noted that the combination score has a prognostic value superior to each of the single parameters separately (Table 1).…”
Section: Discussionmentioning
confidence: 87%
“…We found that stromal categorization that was based on the assessment of tumor-stroma ratio and stromal TILs can serve as a robust tool for prognostication of early OTSCC. Importantly, these two stromal characteristics have shown promising prognostic significance in different subsites of the head and neck cancer [15,[25][26][27][28][29]. We noted that the combination score has a prognostic value superior to each of the single parameters separately (Table 1).…”
Section: Discussionmentioning
confidence: 87%
“…Recently, there is a worldwide research effort to standardize determination of TILs. Many studies have reported that a strong lymphocytic infiltration associates with favorable clinical outcome of different tumors including those of head and neck [18][19][20] . Such favorable outcome could be due to the destruction of cancer cells and anti-tumor effect of the immune response 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: (+ and -) are number of positive and negative patients, *P values in bold represent significant data as calculated using χ 2 or Fisher's Exact Tests, ♣ Numbers between brackets are the percentages of patients Several studies have shown the prognostic value of TIL in various types of solid tumors [9], including Head and Neck cancers [10], and more specifically, NPC [11][12][13][14], although their studies were not devoted to LA-NPC. Wang et al [13] and Almangush et al [15] have studied total TIL in NPC using H&E stained sections and found a high correlation between total TIL and disease outcome using a large cohort (1490 patients). On the other hand, Zhu et al [14], Lu et al [11], and Ono et al [12] investigated specific TIL like CD3+ and/or CD8+ TIL on survival of NPC.…”
Section: Discussionmentioning
confidence: 99%